Influences of welding parameters on distortion. (21st December 2010) - Schimanski, Kai; Von Hehl, Axel; Zoch, Hans-Werner
Laser beam welding (LBW) is an established serial process in manufacturing of parts for aircraft industries, which is characterised by the advantages of weight reduction and shortened process time compared to conventional riveting techniques. However distortions can occur after LBW. Depending on the intensity the distortions impair, e.g., assembly work and aerodynamics behaviour and lead to costly re-shaping procedures. After successful integration of LBW-process in the serial manufacturing process, the aim of running investigations is a basic understanding of the distortion mechanisms during LBW in order to minimise the effort for re-shaping of today's components and to predict the distortion behaviour of future designs. Based on the results of a system-orientated analysis of the process chain first experiments were done to identify the process parameters of LBW-process which significantly influence the final distortion.